Regional distribution of household incomes in Spain from 2008 to 2010 (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
The Great Recession that followed the financial crisis of 2008 has given rise in many countries to declining household disposable incomes. The impact of economic crisis on the household incomes and the redistributive role of the Public Sector are analiyzed in this paper from a spatial point of view
Keywords: household incomes; redistribution; per capita income; autonomous regions; divergence index